HUBUNGAN KELINCAHAN DAN KECEPATAN DENGAN KEMAMPUAN DRIBBLING ATLET SSB PATRIOT MUDA KUOK - Zulfahri Hardi; Zainur Zainur; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The problem in this the research saw that there were still irregularities when dribbling the ball, that is the ball is easily captured by opponents, the ball is always out of control on mastery, too hard to break through the opponents defense,while the training provided by the coach has been maximal. The purpose of this research is to find out whether there is a connection between agility and speed with the ability of ball ability in SSB Patriot Muda Kuok Atlet. The population in this research were 18 football atlet from SSB Patriot Muda Kuok. The sampling technique is saturated sampling, which is a sampling technique if all members of the population are used as samples. Then the sample in this research was set at 18 people. The instrument in this research was agility using the dodging run test, speed with a 50 meter run and the results of dribbling ability. Based on the results of the research that described in the previous chapter, then conclusions can be taken as follows: There is a correlation between agility and dribbling ability, where rtab at significant level α (0.05) = 0.482 means rcount (0.504)> rtab (0.482) . There is a correlation between speed and dribbling ability, where rtab at a significant level α (0.05) = 0.482, means r count (0.607)> rtab (0.482). There is a joint correlation between agility and speed with dribbling ability in the SSB Patriot Muda Kuok football team, where r tab at a significant level α (0.05) = 0.482, means Rhitung (0.634)> rtab (0.482).Key Words: Correlation agility,speed, dribblin ability.